University and Curriculum: The case of Universidad del Tolima (1955-1962) - Giraldo Pérez, Sonia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article aims at presenting an analysis of the curricular structure that came to the first academic programs at the Universidad del Tolima, between 1955 and 1962. It introduces the arguments which bearing in mind political reasons will led them in the birth of the university, once analyzed from a documentary corpus organized around educational legislation and which, at that time, it contributed to guiding the functioning of institutions of professional education. Consequently, we present some programs offered by Universidad del Tolima that configured three of the Faculties of the agricultural field and two technological institutes, all grouped in seven schools. The study suggests that the vicissitudes that happened in this period led the state to redirect educational policies through the invitation of the international Academic Missions that contributed to create educational institutions and so, to allow the creation of universities in some regions of Colombia. The Universidad del Tolima, as  particular case, of the analysis, since its origins, it has sought the development of professionals for the agricultural and technological field.